Effect of milk thistle and silimevit on the functional state and protein synthesizing-function of the liver of laying hens under conditions of cadmium load : ст. - Ostapyuk, A. Y.; Gutyj, B. V. et. al.; Butsyak, A. A.; Popadiuk, S. S.; Senechyn, V. V.; Leskiv, Kh. Ya. (State Scientific-Research Control Institute of Veterenary Medicinal Products and Feed Additives ; Stepan Gzhytskyi National University of Veterinary Medicine and Biotechnologies, 2023)
The purpose of the work was to study the effect of Cadmium on liver function disorders and to develop practical recommendations for using silimevit and milk thistle to reduce the toxic effect of Cadmium on chickens. To achieve the set goal in experiments on chickens under cadmium load, it was necessary to solve the following tasks: to study the effect of Cadmium on the protein synthesis function of the liver of laying hens; to study the effect of Cadmium on the functional state of the liver of laying hens; to investigate the effect of silimevit and the fruits of milk thistle on the functional state of the liver of laying hens under cadmium load; to investigate the effect of silimevit and milk thistle fruits on the protein synthesis function of the liver of laying hens under cadmium load and to justify the use of silimevit and milk thistle to prevent cadmium toxicosis in chickens. Drinking cadmium sulfate to laying hens violates the liver's functional state and protein-synthesizing function. A decrease in total protein and albumin content in their blood was established (Р < 0.001). An increase in alanine and aspartate aminotransferase activity was detected (Р < 0.001). Silimevit and milk thistle positively affect the functional state of the liver of laying hens under cadmium load, as evidenced by a decrease in the activity of aminotransferases in their blood serum. Silimevit and spotted thistle, under the cadmium load of laying hens, positively affect the liver's protein-synthesizing function, evidenced by an increase in total protein and albumin fraction. Feeding laying hens under cadmium load with slime feed contributed to a better-normalizing effect on the activity of aminotransferases and protein-synthesizing function of the chickens' liver than milk thistle.
Keywords: печінка курей-несучок; кадмій; розторопша; сadmium toxicology; liver of laying hens; laying hens